The use of protective face masks in hearing-impaired children during the severe acute respiratory syndrome coronavirus 2 pandemic: a new consideration - Hussain, Tanvir; Munir, Khalid; Patil, Aishan; Munir, Javed (International Journal of Contemporary Pediatrics, 2022)
Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has led a variety of changes in healthcare delivery. Personal protective equipment (PPE) such as the use of face masks has become a new norm in daily life. While this has helped to reduce the transmission of SARS-CoV-2, challenges in social interaction and communication have been identified, especially in those with hearing impairment. This study aimed to identify some of the challenges faced by this COHORT and provided some practical solutions to support these patients. Methods: An observational study was conducted by inviting speech and language therapists (SALTs) to provide their observations on the implications of face masks for children with hearing impairment in Sligo university hospital, Ireland from August 2021 to September 2022. Thirty-three SALTs were invited to participate via the Irish association of speech and language therapists (IASLT) website. Results: Twenty-five responses were received. Common observations include distress amongst parents and children due to difficulties in communication, delays in accessing hearing-aid assessments and cochlear implantation referral and poor compliance with speech and language rehabilitation. Conclusions: This study identifies a number of challenges faced by children with hearing impairment during the current pandemic. A number of practical recommendations have been provided to alleviate and reduce the consequences of these.